Europe was a Woman: National versus Pan-european aspirations as embodied in images of actresses in the Croatian 20th Century Drama - Čale Feldman, Lada (Array, 2000)
The article shows how in the Croatian 20th Century drama actresses arise as emblems of the auto-reflexive, metacultural and metatheatrical national body, oscillating between the idealized but deadening national purity and the promising yet risky transgression of the (territorial and ideological) boundaries imposed on it by its native culture.